Dynamic imine chemistry in metal-organic polyhedral; RSC Advances; Vol. 5, iss. 82 - Vardhan H. Harsh; Mehta A. Akshay; Nath I. Ipsita; Verpoort F. V. K. Frensis Valter Kornelius (2015, 2015)
Title screen